The influence of UMKM budget realization on poverty levels and unemployment rates in East Java province - Ines Almaida; Indrawati Yuhertiana (SEAN Institute, 2024)
The main objective of this study is to investigate how the utilization of the budget allocated for micro, small, and medium enterprises (UMKM) affects the levels of unemployment and poverty in East Java Province. This research employs a quantitative methodology with an explanatory research design. Data collection involves the use of secondary data sourced from the official website of the Department of Cooperatives and SMEs. This secondary data covers a three-year period (2020-2022) and focuses on the UMKM budget utilization across different regions within East Java Province. The analysis of this data utilizes a simple linear regression approach. In the regression analysis testing, two models were examined, namely Model 1 (UMKM Budget realization - Unemployment Rate) and Model 2 (UMKM Budget realization - Poverty Rate). The research results indicate that both the unemployment rate and poverty rate, either partially or simultaneously, do not have a significant impact on UMKM budget realization. Because the significance values ​​obtained for both models are higher than the predetermined significance level (α= 0.05). Therefore, it is recommended that the government conduct a thorough evaluation of UMKM budget policies, strategies, and implementation to understand the factors contributing to the increase in unemployment and poverty rates in East Java Province.